The Mothers' Union goes on strike: Women, tapa cloth and Christianity in a Papua New Guinea society. (21st April 2016) - Barker, John; Hermkens, Anna‐Karina
Abstract : This paper explores the story of the formation and subsequent activities of a church women's group in Maisin villages and women's experiences of Christianity more broadly, in relation to the changing production and uses of traditional bark cloth ( tapa ), a signature women's product which has become a marker of Maisin identity. While the influence of the local Mothers' Union has waxed and waned over the past 60 years, tapa cloth has had a continuing influence upon its fortunes. Tapa cloth has been the chief means for church women to raise funds to support their activities and the local church. However, we argue that, more fundamentally, tapa has shaped women's gendered Christian identities, experiences and history, mediating relationships with men, between generations of women, and with various sorts of 'missionaries' who have often justified their intrusions in terms of improving women's lives.